Arterio-Enteric Fistula in Failed Enteric-Drained Pancreas Transplants: An Impending Danger - Villa, Manuel; Siskind, Eric; Jaimes, Natalia; Eckstein, Donna; Bhaskaran, Madhu; Sachdeva, Mala; Jhaveri, Kenar; Calderon, Kellie; Greben, Craig; Sharan, Lauren; Coppa, Gene; Krishnasastry, Kambhampaty; Molmenti, Ernesto; Nicastro, Jeffrey (International Journal of Angiology, 2014)
Enteric drainage is the preferred method of exocrine diversion in simultaneous kidney–pancreas transplantation. Because of improvements in immunosuppression, enteric drainage has become the preferred method of pancreas transplantation in general. Although associated with less potential complications than bladder-drained pancreas, potentially lethal arterio-enteric fistulas in the setting of nonfunctioning allografts represent a constant threat. We herein present a case report, a review of the literature, and a call for caution.
Keywords: arterio-enteric fistula; enteric-drained pancreas transplant; gastrointestinal bleeding; endovascular stenting; allograft pancreatectomy